Comparison between Partial Newmann Flap Versus Modified Partial Newmann Flap in Mandibular Third Molar Surgery - R. P. Chooni Lal Sharma, Mujtaba Nadeem, Arslan Mahmood, M. Uzair Jamal, S. Kumar Punjabi, S. Aijaz Ali Zaidi, Salman Shams (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the outcomes of two different flap techniques, namely the Partial Newmann Flap (FNP) and the Modified Partial Newmann Flap (MPNF), in surgical extraction of mandibular third molars. Methods: This randomised clinical study included 186 participants, 93 each group. The research comprised male and female patients aged 20–45 with lower mesioangular impacted third molar till 18–21. Patients with vertically impacted wisdom teeth, disto-angular impaction, horizontal impaction, pregnancy, trismus, pericoronitis, and oral submucous fibrosis were excluded. The student t-test compared mouth opening across groups, whereas the chi-square test compared discomfort and edoema. Results: The mean age of the participants was 32.17±8.30 years. On the first day, the MPNF group reported significantly less moderate pain (34.41%) compared to the NPF group (56.99%) (p=0.001). On the third day, the MPNF group reported significantly more mild pain (55.91%) and less severe pain (1.08%) compared to the NPF group, which reported less mild pain (49.46%) and more severe pain (7.53%) (p=0.028). Similarly, mouth opening was significantly higher in the MPNF group than the NPF group on the 1st, 3rd, and 7th day. Swelling was significantly less in the MPNF group than the NPF group on the 1st and 3rd day. Conclusion: The Modified Partial Newmann Flap may be a better alternative compared to the Partial Newmann Flap in terms of pain, swelling, and mouth opening during the disimpaction of lower third molars. Keywords: Partial Newmann Flap, Modified Partial Newmann Flap, Mandibular Third Molar